Hair cortisol concentration is unaffected by basic military training, but related to sociodemographic and environmental factors. (January 2015) - Boesch, Maria; Sefidan, Sandra; Annen, Hubert; Ehlert, Ulrike; Roos, Lilian; Van Uum, Stan; Russell, Evan; Koren, Gideon; La Marca, Roberto
Abstract The analysis of hair cortisol concentrations (HCC) is a promising new biomarker for retrospective measurement of chronic stress. The effect of basic military training (BMT) on chronic stress has not yet been reported. The aim of this study was to investigate the effect of 10-week BMT on HCC, while further exploring the role of known and novel covariates. Young healthy male recruits of the Swiss Army participated twice, 10 weeks apart, in data collection (1st examination: n = 177; 2nd examination: n = 105). On two occasions, we assessed HCC, perceived stress and different candidate variables that may affect HCC (e.g. socioeconomic status, meteorological data). Military training increased perceived stress from the first to the second examination, but did not affect HCC. In line with this, there was no correlation between HCC and perceived stress ratings. This could be interpreted as a missing influence of mainly physical stress (e.g. exercise) on HCC. In contrast, significant correlations were found between HCC and ambient temperature, humidity and education. Future studies should control for meteorological data and educational status when examining HCC.